Kompetensi Manajerial Kepala Madrasah dan Implikasinya pada Kondusivitas Iklim Kerja Guru: Madrasa Principal’s Managerial Competence and its Implications for the Teachers’ Work Climate Conducivity - Fazlur Rahman RM; Muhajir Musa (Madrasah Tsanawiyah DDI Cilellang, 2023)
In the era of regional autonomy, being a principal is no longer a career position but a political one. Managerial competence does not seem to be the main requirement to occupy this position. This study aims to analyze the implications of the madrasa principal’s managerial competence on the conduciveness of the teacher’s work climate. The informants for this phenomenological study consisted of the principal and teachers of the Lamakera State Islamic Junior High School, East Flores, Indonesia. The results showed that the madrasa principal had a good leadership vision, but because the management function in the madrasa program was not optimal, the madrasa principal's managerial competence was low. The teacher's work climate is not conducive because the principal's communication is not effective, madrasah teachers are divided into several groups, there is a lack of ratio of teachers to number of students, administrative work is mostly done by honorary and voluntary teachers, and the allocation of educational operational funds determined by the government is not in accordance with the needs of the madrasa. This research has implications for the need to appoint principals not only based on a training certificate for prospective principals but also on a credible fit and proper test taking into account achievement, experience, and good career paths.